Examining the many dimensions of children's popularity: Interactions between aggression, prosocial behaviors, and gender. (February 2016) - Kornbluh, Mariah; Neal, Jennifer Watling
Using peer nomination data, this study explored predictors of popularity among 144 third- through eighth-grade students in a diverse urban school. Findings demonstrated that children were more likely to be nominated as popular by peers when they exhibited higher levels of prosocial behavior or aggression. Furthermore, a significant interaction between prosocial behavior and aggression predicted popularity. Children with high levels of peer-nominated aggression were more likely to be viewed as popular when they were also nominated by their peers for engaging in high levels of prosocial behavior. Lastly, findings suggested that the positive association between prosocial behavior and popularity was stronger for girls than boys. Implications and areas for future research are discussed.